Reply to the 'Comment on "Revisiting π backbonding: the influence of d orbitals on metal–CO bonds and ligand red shifts"' by G. Frenking and S. Pan, Phys. Chem. Chem. Phys., 2019, 22, DOI: ; 10.1039/C9CP05951B. Issue 9 (20th February 2020) - Koch, Daniel; Chen, Yingqian; Golub, Pavlo; Manzhos, Sergei
Abstract : We respond to the comment by Pan and Frenking with regard to our investigation on transition and alkaline earth metal d orbital influence on their bonding to carbonyl ligands to clarify misconceptions. Abstract : We respond to the comment by Pan and Frenking with regard to our investigation on transition and alkaline earth metal d orbital influence on their bonding to carbonyl ligands to clarify misconceptions. We do not consider the points raised in the comment as affecting our conclusions.